ESSENCE AND FEATURES OF THE GAME AS A CHILDRENʼS ACTIVITY (Scientific journal of the Fergana State University, 2023)
Game is the main and most favorite pastime of preschool children. Therefore, the introduction of game elements and problem situations in the educational process enlivens learning. The article presents some views and decisions about the essence and originality of the game as a childʼs activity.